2011
DOI: 10.1016/j.jcrs.2011.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive keratectomy in treatment of refractive amblyopia in the adult population

Abstract: After PRK to eliminate and correct refractive errors in anisometropic amblyopia, visual acuity improved significantly in 70% of adult patients with no previous occlusion or chemical penalization treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The localization and adhesion of the embryo to the epithelial cells is the first step in the initiation of implantation. Suboptimal embryo adhesion is widely thought to be a major cause of implantation failure 25 , 26 . Studies have shown that many factors are involved in regulating embryo adhesion processes.…”
Section: Discussionmentioning
confidence: 99%
“…The localization and adhesion of the embryo to the epithelial cells is the first step in the initiation of implantation. Suboptimal embryo adhesion is widely thought to be a major cause of implantation failure 25 , 26 . Studies have shown that many factors are involved in regulating embryo adhesion processes.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of the increase in CDVA is unclear, but the reason for the improvement may be the relative magnification of the image after an anterior chamber pIOL implantation when compared with spectacle lenses [ 14 ]. There is agreement in the literature that improvement occurs in CDVA after corneal refractive surgery or pIOL implantation [ 15 17 ].…”
Section: Discussionmentioning
confidence: 98%
“…Although the exact mechanism is unclear, the relative magnification of the image and the reduction in visual aberrations after an anterior chamber pIOL implantation when compared to spectacle lenses may be the reason for the improvement [ 20 ]. In addition, the studies in the literature that evaluate CDVA improvement in adult amblyopic eyes after laser-assisted in situ keratomileusis (LASIK), photorefractive keratectomy (PRK), or pIOL implantation agree that improvement occurs; however, the rates vary over a wide range [ 19 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%